C++, a better language for engineering applications. - Erricolo, Danilo (IEEE Antennas & propagation magazine.)
In this review, we show the features of C++ that make it superior in comparison with other languages. Use of data hiding and objects are an important way to improve the quality of the software that is produced, because the final product is easier to develop, maintain, document, and upgrade. Because of the overloading mechanism, the elegance of some notations-such as in the example of the product among vectors and matrices-is now available, even when writing a computer program. In addition, the Standard Template Library provides a huge set of templates that save a great deal of time in the development of software. Here, only the features of C++ that are relevant to engineering applications have been briefly introduced with some examples.